Τὸ πλαίσιο ἐφαρμογῆς τῆς προσφυγικῆς ἐγκατάστασης καὶ ἀποκατάστασης καὶ ἡ ἐπιβολὴ ἐθνοτικῆς καὶ χωρικῆς ὁμοιογένειας στὴ Θρακικὴ ἐπαρχία (1922-1930) - Κουτσούκος, Βασίλης (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
The population exchanges between Bulgaria and Greece and Turkey and Greece during the early 1920s functioned as an excellent opportunity for the rival Balkan states to meet the doctrines of nation-state formation. In this specific case Greek Thrace is investigated as a province with a historically formed ethnic composition that questioned the attempts of the Greek authorities to establish their national dominance, semiological representation and function. Under the urgency of the refugees’ presence the Greek state put into operation a massive colonisation and homogenisation project aiming to unbalance the regional ethnic diversity, to restrict the minority semiological representation, to link and administer local institutional (communal and municipal) and governmental bodies with the national ones and to regulate the Thracian landscape according to the national archetype. Seizures, requisitions, appropriations and redemptions of movable and immovable properties were the key tools adopted by a network of state institutions and the dominant group members themselves. During an eight-year period the colonisation and homogenisation project achieved an ambiguous implementation and introduced a new revised project under the latest diplomatic developments between the Balkan states. Extensive archival resources and various published materials have been elaborated in an attempt to reveal the utility of space as a fundamental tool towards the accomplishment of the incorporation of a newly annexed ethnically diverse province into a nation-state.